Ultrasound mediated Green synthesis of Hexa-hydro Triazines - Singh K. A.K.; Shukla K. S.K.; Quraishi M.A. (My University, 2025)
Sym-triazines have been documented for their antitumor, antimicrobial and anti-cancer actions. The present work aims to derive a variety of 1,3,5-triaryl-1,3,5-hexahydrotriazine using ultrasound assisted reactions from the reactions of aryl amines with aqueous formaldehyde. Furthermore, a special study on the different solvents and revealed that mixture of water and ethanol was found to be the best solvent.